Heavy metal stabilized sewage sludge compost as a growth medium for ornamentals - Rehana M R (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 2019)
The present investigation entitled “Heavy metal stabilized sewage sludge compost as a growth medium for ornamentals” was conducted in the department of Soil Science and Agricultural Chemistry, College of Agriculture, Vellayani during 2017-2019 with the objective to prepare and characterize heavy metal stabilized sewage sludge compost and to utilize it as a growth medium for marigold. Sewage sludge for the study was obtained from sewage treatment plant, Muttathara Thiruvananthapuram. The study comprised of two parts viz, preparation of sewage sludge compost and the evaluation of the suitability of the compost as a component for growing media for ornamentals. The composting experiment was laid out in completely randomized block design with eight treatments and three replications. The treatments consisted of sewage sludge + coir pith (50:50) + lime (T1 - compost 1), sewage sludge + coir pith + zeolite (50:30:20) + lime (T2 - compost 2), sewage sludge + sawdust (50:50) + lime (T3 - compost 3), sewage sludge + sawdust + zeolite (50:30:20) + lime (T4 - compost 4), sewage sludge + coir pith (50:50) + fly ash (T5 - compost 5), sewage sludge + coir pith+ zeolite (50:30:20) + flyash (T6 - compost 6), sewage sludge + sawdust (50:50) + flyash (T7 - compost 7) and sewage sludge + sawdust + zeolite (50:30:20) + flyash (T8 - compost 8). In the second phase, growing media prepared using the sewage sludge composts and soil in 1:1 ratio were taken as treatments and evaluated using marigold as test crop. The nine treatments were T1 - soil + sewage sludge, T2 - soil + compost 1, T3 - soil + compost 2, T4 - soil + compost 3, T5 - soil + compost 4, T6 - soil + compost 5, T7 - soil + compost 6, T8 - soil + compost 7 and T9 - soil + compost 8. The design adopted was CRD with three replications. Characterisation of sewage sludge generated from Muttathara treatment plant revealed that the sludge had a pH of 5.36. The organic carbon content was high (17.03%). It was rich in plant nutrients N (1.68%), P (7.73%), K (1.2%), Ca (12%), Mg (4.8%), S (616 mg kg-1), Fe (4500 mg kg-1), Mn (1028.8 mg kg-1), Zn (220 mg kg-1), Cu (250 mg kg-1) and B (23.06 mg kg-1). The sludge contained heavy metals Pb (73.2 mg kg-1), Cr (113.2 mg kg-1), Ni (122 mg kg-1) and Cd (10.8 mg kg-1). Cr, Ni and Cd were above critical limit. As was not detected. The results of composting experiment revealed that T7 (Sewage sludge + coirpith (50:50) + flyash) recorded the highest organic carbon percentage (14.47%) followed by T5 (14.42%). Composting resulted an increase in pH. In the final compost T2 recorded the lowest pH (5.23) and the highest pH was noticed in T8 (7.07). Content of major nutrients, secondary nutrients, micro nutrients and heavy metals increased in the final compost. T8 recorded the highest amount of nitrogen (1.53%), phosphorus (1.24%) and potassium (0.29%). T8 (sewage sludge + sawdust + zeolite (50:30:20) + flyash) recorded the least concentration of heavy metals lead (33.06 mg kg-1), nickel (97.623 mg kg-1), cadmium (5.41 mg kg-1), and chromium (47 mg kg-1). E. coli was not detected in any one of the treatments. Heavy metal fractionation studies of final compost revealed that the mobile fractions of heavy metals (exchangeable and carbonate) decreased in all treatments while the stable fraction of heavy metal (residual) increased. Mobile fractions of lead decreased during composting and was found to be least in T8 and T2. Exchangeable and carbonate fractions of chromium decreased during composting and was found to be lowest in T8 (0.043 and 0.047 mg kg-1 respectively). Exchangeable fraction of nickel was found to be lowest in T6 (0.070 mg kg-1) while carbonate fraction (1.036 mg kg-1) was lowest in T8. In case of cadmium, exchangeable (0.010 mg kg-1) and carbonate (0.013 mg kg-1) fractions were found to be least in T8. Results of pot culture experiment revealed that there was a reduction in pH, electrical conductivity, organic carbon and content of all nutrients in growing media at the end of the experiment. Dehydrogenase activity increased in the post harvest growing media compared to initial for all treatments. T9 (Soil + compost 8) recorded the maximum no of flowers, flower yield, flower weight, flower diameter and took least number of days to first flowering. It was also superior with respect to vegetative and floral parameters. The heavy metal content in plant (shoot and root) were significantly influenced by the treatments and T1 (soil + sewage sludge) recorded the highest content for all heavy metals and was above the permissible limit for Cd, Cr and Pb. The lowest heavy metal content in shoot and root were observed in T9 (soil + compost 8) and was within the permissible limits for all the treatments T2 to T9. Arsenic was not detected in shoot and root in any of the treatments. Lead content was also not detected in roots. Based on the present investigation it can be concluded that sewage sludge generated from sewage treatment Muttathara is rich in organic carbon and other plant nutrients and had a pH of 5.36. The sludge contained heavy metals such as Pb, Cr, Ni and Cd of which Cr, Ni and Cd were above the critical limit. Sewage sludge compost prepared as per the treatments were rich in organic carbon and plant nutrients. During composting there was a drastic reduction in the mobile fractions (exchangeable and carbonate) and an increment in stable fractions (residual) which indicated that composting of sewage sludge with heavy metal adsorbent and different bulking agents decreased the mobility and bioavailability of heavy metals. Results of pot culture experiment indicated that the growth and yield of marigold was higher in the treatment receiving sewage sludge, sawdust, zeolite (50:30:20) and flyash. The heavy metal content in marigold were found to be below the permissible limit in all the treatments indicating that composting of sewage sludge with bulking agents like coirpith, sawdust and adsorbents like zeolite decreased the uptake of heavy metals by plants.